دراسة مشكلة عدم التوافق الذاتي عند صنف الزيتون الخضيري وبعض أصناف الزيتون المُلقحة. - استنبولي أحمد علي; القيم فاضل سليمان; أبو الشملات ربى أمير (Latakia University Journal -Biological Sciences Series, 2014)
ظهرت مشكلة عدم التوافق الذاتي عند صنف الزيتون الخضيري المزروع بكثرة في محافظة اللاذقية. وعند دراسة هذه الظاهرة على صنف الخضيري في منطقتي (جبلة وبوقا)، بينت النتائج أن صنف الخضيري عقيم ذاتياً أي أنه غير قادر على تلقيح نفسه أو أزهار أشجار أخرى من نفس الصنف والثمار الناتجة صغيرة جداً ولا تحتوي على بذور. كما أظهرت النتائج أن ظاهرة إجهاض المبايض عند أزهار الصنف الخضيري عائدة للعامل الوراثي للصنف. تم خلال البحث دراسة درجة التوافق الذاتي عند بعض أصناف الزيتون لاستخدامها كملقحات لصنف الخضيري، فكانت النتيجة أن صنف الجلط والصفراوي والصوراني متوافقة جزئياً، وذات توافق عالٍ مع الصنف الخضيري، ومنه ننصح بزراعة هذه الأصناف الملقحة بين حقول الزيتون لتحسين نوعية الثمار وزيادة الإنتاج عند صنف الخضيري. The self-incompatibility problem appeared in the Khodeiry variety widely grown In Lattakia. When this phenomenon was studied on the Khodeiry variety in two areas (Jabla and Boqa), the results showed that this variety is self-sterile, i.e. it is not able to pollinate itself or the flowers of other trees of the same variety, and its fruit is very small and do not contain seeds. The results also showed that the flower abortion percentage in the Khodeiry variety is due to the genetic factor which varies depending on the variety. The study investigated the self-compatibility in some olive varieties in order to use them as pollinizers for the Khodeiry variety with the result that the Gellet, Soufrawy and Sourany varieties are particularly compatible and have a high compatibility with the Khodeiry variety. Based on these results, it is recommended that pollinated varieties are grown between olive orchards to improve fruit and to increase its production